McNamara analysis cephalometric parameters in White-Brazilians, Japanese and Japanese-Brazilians with normal occlusion - Juliana Moura STORNIOLO-SOUZA; Maria Pia SEMINARIO; Célia Regina Maio PINZAN-VERCELINO; Arnaldo PINZAN; Guilherme JANSON (Dental Press Editora, 2021)
ABSTRACT Introduction: McNamara's Jr. cephalometric analysis is a tool to diagnose dental and skeletal discrepancies and is widely used, guiding diagnosis for surgical procedures to be performed or for the use of functional devices. Few studies have shown that different ethnic groups have different cephalometric patterns. Thus, single characteristics should be respected to support the diagnosis and to help the treatment plan for different ethnic groups and their different patterns of miscegenation. Objective: Obtain normal values for McNamara's cephalometric analysis for adolescent Japanese-Brazilian descents with normal occlusion, as well as to compare this sample with similar samples of White-Brazilian and Japanese. Methods: Lateral headfilms from 40 White-Brazilian, 33 Japanese and 32 Japanese-Brazilian descents were selected. The three groups were composed by individuals with normal occlusion, well-balanced profiles and were separated by sex. The data were statistically analyzed with ANOVA, t-test, ANCOVA and MANCOVA tests. Results: White-Brazilian males had significantly greater nasolabial angle than Japanese males. Japanese-Brazilian displayed an intermediate value between White-Brazilian and Japanese. Conclusion: White-Brazilian, Japanese and Japanese-Brazilian present different cephalometric characteristics of McNamara analysis. Japanese males have a significantly more acute nasolabial angle than White-Brazilian subjects.